Boundedness in Lebesgue spaces of Riesz potentials on commutative hypergroups - Hajibayov, Mubariz (Global Journal of Mathematical Analysis, 2015)
In the present paper we consider Riesz potentials on commutative hypergroups and prove the boundedness of these potentials from \(L^{p} \left( K,λ \right) \) to \(L^{q} \left( K,λ \right) \). We also prove the inequality from \(L^{1} \left( K,λ \right) \) to weak \(L^{q} \left( K,λ \right) \) for Riesz potentials on commutative hypergroups.